Explaining variation and change in supervisory confidentiality in the European Union. Issue 4 (4th July 2018) - Gandrud, Christopher; Hallerberg, Mark
Abstract: Some European Union member states' financial regulators choose to make some of the data they routinely collect on individual banks publicly available. Others treat this data as confidential. What explains this difference? This paper considers the possible effects of crises, path-dependent legal institutions, and the design of deposit insurance schemes. At the national level, the paper focuses on contrasting German and Dutch cases. After the recent economic crisis, the Dutch released more data while the German authorities maintained strict confidentiality rules. The design of deposit insurance schemes provides a key reason why the level of secrecy varies, with the Dutch move from an ex post to an ex ante scheme where the government served as the ultimate backstop leading to questions about the accounts of individual banks while the German system favoured continued secrecy. The paper also describes the level of transparency at the EU level. Multilevel legal restrictions and bureaucratic capacity tilt EU banking union practices towards member states that treat financial supervisory data as confidential.